Communication Skill for Excellent Service (PKK dan BUMDes di Desa Sukaraharja Kabupaten Tasikmalaya) - Rakista, Putri Mutiara (Jurnal Abdimas Pariwisata, 2024)
Communication Skill For Excellent Service (Pengelola Organisasi Wisata Di Desa Sukaraharja Kabupaten Tasikmalaya) Communication skills training to improve good service is considered important to be carried out in Sukaharja Village as an improvement in the quality of human resources in organizations in the Sukaharja Village Community as well as developing the quality of human resources. Communication skills are needed to provide excellent service to the end of the village and provide excellent service to customers who are interested in the products produced by the village, as well as an effort to introduce the potential of the village. The Community Service Method (PKM) is carried out in the form of counseling and training which begins with planning, implementation and evaluation. The results of this activity have an impact on increasing insight and soft skills, especially in the field of communication in the community managing community organizations in Sukaharja Village, Cisayong District, Tasikmalaya Regency.